Using Text with Pictures in Primary School to Improve Reading Comprehension for Hearing Impaired Students - Abdul Rahim Razalli; Renate Olga Thomas; Nordin Mamat; Noreha Yusuf (Department of Special Education, 2018)
The objectives of the study are to determine whether using text with pictures is effective to improve reading comprehension for students with hearing impairment, to examine other strategies that can support the development or improvement of reading comprehension for students with hearing impairment and to determine the factors affecting reading comprehension for students with hearing impairment. A qualitative research design was chosen to answer three research questions. Two sets of instruments (observational checklist and interview questionnaires) have been used to obtain information of reading comprehension and factors that influence it. Six hearing impaired students and five teachers were selected as the respondents through purposive sampling technique. The findings show that text with pictures can help to improve reading comprehension for students with hearing impairment. The implications of this study show that text with pictures motivate students with hearing impairment to read and it have to be encouraged in primary school. A more comprehensive study should be undertaken for higher order thinking skills and the use of interactive models for reading comprehension lessons for students with hearing impairment.skills are across all subjects.